1988
DOI: 10.1007/bf00174516
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of taste factors and gender to opioid preference in C57BL and DBA mice

Abstract: C57BL/6J and DBA/2J mouse strains have been characterized as morphine preferrers and avoiders, respectively (Horowitz et al. 1977). Previously, sweetened morphine solutions were presented with a water alternative, primarily with male subjects. Because sweetness may affect the endogenous opioid system and rodents have shown strain and sex differences in taste preferences, this study looked for strain- and gender-related taste preferences that might have affected opiate consumption. Preference for sweetened and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
28
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 17 publications
4
28
0
1
Order By: Relevance
“…The observation that the C57BL/6 strain consumed more nicotine than did any of the other strains is not surprising given that C57BL/6 mice also show high consumption of other psychoactive drugs such as ethanol (McClearn and Rodgers 1959;Rodgers and McClearn 1962;Pickett and Collins 1975;Lfi et al 1994;Meliska et al 1995), morphine (Horowitz et al 1977;Forgie et al 1988), cocaine (Morse et al 1993), and amphetamine (Meliska et al 1995) when given a choice between drugcontaining solutions and vehicle. However, the finding that DBA/2 mice had the second highest level of consumption is somewhat surprising, since this strain totally avoids ethanol (Rodgers and McClearn 1962;Pickett and Collins 1976), morphine (Forgie et al 1988), cocaine (Morse et al 1993), and amphetamine (Meliska et al 1995).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The observation that the C57BL/6 strain consumed more nicotine than did any of the other strains is not surprising given that C57BL/6 mice also show high consumption of other psychoactive drugs such as ethanol (McClearn and Rodgers 1959;Rodgers and McClearn 1962;Pickett and Collins 1975;Lfi et al 1994;Meliska et al 1995), morphine (Horowitz et al 1977;Forgie et al 1988), cocaine (Morse et al 1993), and amphetamine (Meliska et al 1995) when given a choice between drugcontaining solutions and vehicle. However, the finding that DBA/2 mice had the second highest level of consumption is somewhat surprising, since this strain totally avoids ethanol (Rodgers and McClearn 1962;Pickett and Collins 1976), morphine (Forgie et al 1988), cocaine (Morse et al 1993), and amphetamine (Meliska et al 1995).…”
Section: Discussionmentioning
confidence: 89%
“…However, the finding that DBA/2 mice had the second highest level of consumption is somewhat surprising, since this strain totally avoids ethanol (Rodgers and McClearn 1962;Pickett and Collins 1976), morphine (Forgie et al 1988), cocaine (Morse et al 1993), and amphetamine (Meliska et al 1995). These results argue that the genetic influences on nicotine intake are not identical to the genetic influences on intake of these other drugs.…”
Section: Discussionmentioning
confidence: 94%
“…B6 mice consume large amounts of sweeteners (Lush 1989;Bachmanov et al 1996aBachmanov et al , 1996b, alcohol (Belknap et al 1993;Bachmanov et al 1996aBachmanov et al , 1996b and morphine (Forgie et al 1988) compared with the other mouse strains, and genetic correlations have been found between sweetener and alcohol intake in mice (Belknap et al 1993;Blizard and McClearn 1996;Bachmanov et al 1996a), suggesting that these behaviors may be affected by a common mechanism. However, quantitative trait loci modulating alcohol and morphine preference of B6 mice have been localized to Chrs 1, 2, 6, 10, and 11, but not to Chr 4 (Berettini et al 1994;Melo et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have indicated that alcohol-preferring Lewis rats consume more cocaine and opioids than the alcohol-avoiding Fischer rats (George and Goldberg 1988;George 1991;Suzuki et al 1992). Similar differences in the intake of these drugs have been found between C57BL/6J and DBA/2J mice that differ in their alcohol preference (Eriksson and Kiianmaa 1971;Horowitz et al 1977;Whitney and Horowitz 1978;Forgie et al 1988;Belknap 1990;Carney et al 1991). Conversely, rats of a line bred for high morphine consumption selected twice as much alcohol after deprivation than those of a line bred for low morphine intake (Nichols and Hsiao t967).…”
mentioning
confidence: 68%
“…Many procedures to establish oral etonitazene and cocaine as reinforcers have been described, including adjunctive training procedures (George and Goldberg 1988;George 1991;Suzuki et al 1992), pre-exposure to ethanol (Meisch et al 1990;George et al 1991), scheduleinduced polydipsia (McMillan and Leader 1976;Meisch and Stark 1977;Tang the Falk 1987), and several variations of the two-bottle paradigms (Forgie et al 1988;Belknap 1990;Carney et al 1991). Etonitazene has a barely perceptible bitter taste at concentrations that produce behavioral effects (McMillan and Leander 1976); cocaine has a strong bitter taste but nevertheless is also readily ingested orally at low concentrations.…”
mentioning
confidence: 98%